Adequacy of CPF savings and other retirement issues. - Ng, Janice Ching Xin. (2008)
The government has recently introduced some changes to the CPF system. How are these changes going to affect Singaporean’s retirement plan? In our research, we seek to follow-up with the past research onSingaporean’s ability to retire comfortably based on their CPF savings and to look at some recent changes to the rules and regulations of CPF system.